2020
DOI: 10.1038/s41598-020-75712-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive attitudes and negative expectations in lonely individuals

Abstract: Loneliness is a central predictor of depression and major factor of all-cause mortality. Loneliness is supposed to be a warning signal prompting individuals to seek out social connections. However, lonely individuals seem to be less likely to engage in prosocial activities and are overall more socially withdrawn. Hence, it is yet unclear whether and how loneliness affects an individual’s social motivations. Prosocial attitudes and expectations about social interactions of lonely individuals might shed light on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Perception of loneliness is defined as an individual and subjective experience which is highly prevalent in old age and in people with emotional disorders; however, it also affects younger people. 17 , 19 , 32 , 33 It has been related with mental health deterioration, low self-esteem, sleep disorders, depression, suicide attempts, poor quality of life, cardiovascular morbidity and increases the risk for all-cause mortality. 12 , 16 , 17 , 20 , 21 , 34 Weiss 33 determined that emotional loneliness is the loss or absence of a close person, a generator of emotional attachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perception of loneliness is defined as an individual and subjective experience which is highly prevalent in old age and in people with emotional disorders; however, it also affects younger people. 17 , 19 , 32 , 33 It has been related with mental health deterioration, low self-esteem, sleep disorders, depression, suicide attempts, poor quality of life, cardiovascular morbidity and increases the risk for all-cause mortality. 12 , 16 , 17 , 20 , 21 , 34 Weiss 33 determined that emotional loneliness is the loss or absence of a close person, a generator of emotional attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 17 , 43 , 44 describe that in addition to the social network size, the quality of personal interrelationships affects feelings of loneliness and the effect generated by distancing and social isolation. A meta-analysis by Pinquart and Sörensen 45 suggests that the quality of social relationships has an explanatory power for loneliness that is three times higher than that of the number of social contacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is a type of loneliness sought by individuals, purposefully without someone or something, resulting in the simple satisfaction and fulfillment in being alone. 12,13 Some authors 7 have found that loneliness perception increases the risk of all-cause mortality (HR = 1.22, 95%CI: 1.10-1.35). In this regard, loneliness has been associated with poor quality of life, and general morbidity including cardiovascular but most significantly coronary disease.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the perception of loneliness and social isolation may be stressors that trigger negative reactions, specifically: anxiety, fear, moodiness, depression, irritability, hostility, mistrust, suicide attempts, and low self-esteem. [9][10][11][12][14][15][16][17][18][19] These reactions are related to sleep disorders (SD), because they disrupt sleep and increase the possibility of non-restorative sleep. 9 Sleep disorders include difficulty in falling asleep, difficulty in remaining asleep through the night, and waking up early.…”
Section: Introductionmentioning
confidence: 99%